Profile of Children With Non-alcoholic Fatty Liver Disease Referred to a Hospital in Iran - Amin Ghanbari; Mohammadreza Pazoki; Bahar Allahverdi; Pejman Rohani; Parisa Rahmani (علوم بهداشتی ایران)
Background and Purpose: Non-alcoholic fatty liver disease (NAFLD) has become a health concern in children and adolescents. Early detection and intervention are crucial to prevent its long-term complications. This study aimed to identify demographic, clinical, and laboratory characteristics of children with NAFLD referred to a hospital in Iran. Materials and Methods: This descriptive cross-sectional study was conducted on 66 children with NAFLD aged ≤18 years referred to Children’s Medical Center in Tehran, Iran during 2021-2022. The NAFLD diagnosis was via ultrasound or liver biopsy. Demographic and laboratory data were collected from an electronic health record system, and lifestyle information (physical activity (PA) and nutrition) was gathered using a standardized screening questionnaire. Statistical tests such as chi-square, Fisher’s exact, independent sample t-test, and ANOVA were performed in SPSS software, version 27. The significance level was set at 0.05. Results: The majority of children were male (74%), with a mean age of 118.04±42.01 months and a mean BMI of 26.37 kg/m2 (75.93% overweight). A significant proportion of participants had a family history of fatty liver disease (57.4%). Children’s PA level was low; 50% engaged in less than 420 minutes of PA per week. Eating habits were also concerning; 68.5% eat fast food and sweets almost daily. Laboratory findings revealed elevated levels of alanine transaminase (ALT), triglycerides (TG), and total cholesterol (TC) (60.72±59.06 U/L, 65.35±142.54 mg/dL, 35±166.71 mg/dL, respectively). Conclusion: This study highlights the importance of considering family history and metabolic markers in NAFLD diagnosis and management. Most of the children with NAFLD referred to the study hospital were male with a family history of NAFLD and elevated liver enzymes and lipid levels.